1990
DOI: 10.1016/0043-1648(90)90083-m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of transfer film formation during repeat pass sliding of ceramic materials

Abstract: The formation of transfer film and the consequent effects on the friction and wear behavior of ceramic materisIs during repeat sliding contact were studied. This was done using four structuraI ceramics, namely silicon nitride, silicon carbide, ahunina and zirconia, with a cylinder-on-flat test configuration. The transfer film consists of reattached fme wear debris particles, the film, whenever formed, is strongIy attached, enough to resist being wiped off by the slider. Cahxdations suggest that the Sne particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 16 publications
2
35
2
2
Order By: Relevance
“…In addition, it has been reported that oxide wear debris generated in a humid environment contains some level of hydration and the hydroxide component of the wear debris exhibits lower friction than the pure oxide alone [24,25]. In the sliding wear of TiAlCrYN, coatings being tested at RH = 33% showed lower wear coefficients than those tested at RH = 23% (Table 2).…”
Section: Influence Of Tribofilm Formation On Friction and Wear Mechanmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition, it has been reported that oxide wear debris generated in a humid environment contains some level of hydration and the hydroxide component of the wear debris exhibits lower friction than the pure oxide alone [24,25]. In the sliding wear of TiAlCrYN, coatings being tested at RH = 33% showed lower wear coefficients than those tested at RH = 23% (Table 2).…”
Section: Influence Of Tribofilm Formation On Friction and Wear Mechanmentioning
confidence: 94%
“…The TiAlCrYN coatings exhibited wear coefficients in *10 -16 m 3 N -1 m -1 scale at relative humidity of 30%-33%, whereas a small decrease of the humidity to 23%-25%, led to considerably higher wear coefficients in the scale of *10 -15 m 3 N -1 m -1 . It was reported in literature that water molecules can be absorbed on the wear debris and tribofilm to result in lower severity of adhesive interaction within the sliding contact zone [24,25].…”
Section: Friction and Wear Propertiesmentioning
confidence: 99%
“…It was thought that the cracks would propagate along areas of weakness in the underlying material under cyclic stress due to the strong adhesion between the transferred surface layer and the underlying material, i.e., a fatigue process was involved 19 . Since the intersplat bonding is weak in the plasma-sprayed ceramic coating 20,21 , the delamination was along the splat boundary, and accordingly, a large crater was produced. It was inferred that the wear rate of the coating would increase if the sliding distance was increased.…”
Section: Friction and Wearmentioning
confidence: 99%
“…Here dS i /dt is entropy production as a result of the distribution of heat and other flows within a body; dS e /dt-flow of entropy due to external impact, which could change due to the transition of heat from a hotter friction surface into a colder body (the cutting tool) and which results in an increase of entropy; dS m /dt-change of entropy due to the formation of chemical compounds on the tool surface due to the entropy of the matter from the contacting frictional body (in our case, it is mostly due to cutting tool-chip interactions with further formation of seizure zones or buildups [165,176,177]); dS f /dt-change of entropy due to tribofilm formation; dS w /dt-change of entropy due to wear process (the '−' sign is used in the equation because the wear products leave the frictional body with their own entropies). The change of entropy, dS f /dt, could be negative, if nonequilibrium processes are taking place on the surface and entropy of a frictional body is reduced, or positive, if the equilibrium processes are going along [174].…”
Section: Tribofilms (Secondary Structures)mentioning
confidence: 99%